Premium Pricing of Liability Insurance Using Random Sum Model - Mujiati Dwi Kartikasari (EKSAKTA: Journal of Sciences and Data Analysis, 2017)
Premium pricing is one of important activities in insurance. Nonlife insurance premium is calculated from expected value of historical data claims. The historical data claims are collected so that it forms a sum of independent random number which is called random sum. In premium pricing using random sum, claim frequency distribution and claim severity distribution are combined. The combination of these distributions is called compound distribution. By using liability claim insurance data, we analyze premium pricing using random sum model based on compound distribution